Model-Informed Development of Sotalol Loading and Dose Escalation Employing an Intravenous Infusion - Somberg, John C. (Cardiol Res, 2020)
BACKGROUND: Sotalol is often employed to prevent recurrence of symptomatic atrial flutter/atrial fibrillation. Because sotalol can prolong the QT interval excessively causing ventricular arrhythmias, a 3-day in-hospital loading or dose escalation period is mandated with oral administration in the product label for patient safety. In patients with normal renal function, 3 days (five oral doses) are required to obtain steady state maximum sotalol concentration, which results in maximum QT prolongation. The aim of this study is to develop an intravenous to oral loading regime for sotalol therapy that reduces the 3-day in-hospital initiation or dose escalation with oral administration to 1 day without compromising patient safety. METHODS: Using model-informed drug development techniques, simulations were developed for initiation and dose escalation of sotalol therapy by employing an intravenous loading dose followed by oral sotalol administrations. RESULTS: In patients with normal renal function, an initial 1-h loading dose of intravenous sotalol followed by two oral doses in 24 h has been developed permitting attainment of three maximum serum concentrations reflecting maximum QT prolongation in a 1-day observation period. Dosing regimens for patients with impaired renal function are also developed. CONCLUSIONS: In patients with normal renal function, using an intravenous loading dose followed by oral administrations permits safe initiation or dose escalation of sotalol in 1 day instead of the 3-day dosing regimen with oral administration.